2006
DOI: 10.1002/path.2113
|View full text |Cite
|
Sign up to set email alerts
|

Collagen loss and impaired wound healing is associated with c‐Myb deficiency

Abstract: Collagen type I serves as an abundant structural and signalling component of skin. It is also an established target gene of the transcription factor, c-Myb. When c-myb-/- embryos were examined it was observed that their skin was markedly thinner than normal. Importantly, immunohistochemical investigation showed complete absence of collagen type I. Although these homozygous knock-out embryos fail to develop beyond day 15, fibroblasts established from these embryos (mouse embryonic fibroblasts [MEFs]) show defec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
53
0
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 62 publications
(54 citation statements)
references
References 24 publications
0
53
0
1
Order By: Relevance
“…The skin of heterozygous c-Myb-deficient mice exhibits impaired wound-repair capability and reduced collagen type I levels. C-Myb-deficient wounds show reduced fibroblast cell proliferation and collagen levels, but the TGF-β1 expression levels are elevated [48]. Ma HH et al have reported that the antisense RNA of c-Myb suppressed collagen I-a1 expression in cultured hepatic stellate cells [49].…”
Section: Discussionmentioning
confidence: 99%
“…The skin of heterozygous c-Myb-deficient mice exhibits impaired wound-repair capability and reduced collagen type I levels. C-Myb-deficient wounds show reduced fibroblast cell proliferation and collagen levels, but the TGF-β1 expression levels are elevated [48]. Ma HH et al have reported that the antisense RNA of c-Myb suppressed collagen I-a1 expression in cultured hepatic stellate cells [49].…”
Section: Discussionmentioning
confidence: 99%
“…As mentioned earlier, a role for collagen I in promoting COX-2 expression in gestational breast cancer has been defined [83]. Collagen I (COL1A2) is a target gene of c-Myb [134], thus a c-Myb-Collagen I-COX-2 inductive pathway may serve as an alternative means through which cMyb may indirectly govern the expression of COX-2 in breast cancer. Taken together, these findings lend support to the notion that the c-Myb-COX-2 inductive relationship may extend beyond colorectal cancer.…”
Section: Putative C-myb-cox2 Pathwaymentioning
confidence: 99%
“…Wound-healing and random cell migration assays were performed essentially as described previously (Pankov et al, 2005;Kopecki et al, 2007) by using an AxioCam MRm camera (Carl Zeiss) on an Axiovert 200 automatic microscope equipped with closed heating and CO 2 perfusion devices. Maximal wound closure rates corresponded to normalized slopes of linear equations derived from regression analyses of the area over time plots shown in Figure 11B.…”
Section: Video-and Electron Microscopy and Microinjectionmentioning
confidence: 99%
“…Fluorescent recovery after photobleaching (FRAP) experiments were performed on a dual-headed, confocal microscope (FluoView 1000; Olympus, Hamburg, Germany) with cells cotransfected (overnight) with myc-tagged L61-Rac1 and EGFP-actin or EGFP-p16B at a ratio of 2:1, and analyzed as described previously (Lai et al, 2008). Wound-healing and random cell migration assays were performed essentially as described previously (Pankov et al, 2005;Kopecki et al, 2007) by using an AxioCam MRm camera (Carl Zeiss) on an Axiovert 200 automatic microscope equipped with closed heating and CO 2 perfusion devices. Maximal wound closure rates corresponded to normalized slopes of linear equations derived from regression analyses of the area over time plots shown in Figure 11B.…”
mentioning
confidence: 99%